Association of GALC, ZNF184, IL1R2 and ELOVL7 With Parkinson’s Disease in Southern Chinese - Li, Gen; Cui, Shishuang; Du, Juanjuan; Liu, Jin; Zhang, Pingchen; Fu, Yang; He, Yixi; Zhou, Haiyan; Ma, Jianfang; Chen, Shengdi (Frontiers in Aging Neuroscience, 2018)
Study Objectives: The aim of the study was to investigate the relationship between 22 single nucleotide polymorphisms (SNPs) and Parkinson’s disease (PD) in the Chinese population. Methods: A total of 250 PD patients and 240 healthy controls were recruited. The SNaPshot technique and the polymer chain reaction were used to detect 22 SNPs. Results: rs8005172 of GALC, rs9468199 of ZNF184 and rs34043159 of IL1R2, were associated with PD (rs8005172: p = 0.009, OR = 0.69, allele model, p = 0.010, additive model, p = 0.015, OR = 2.17, dominant model; p = 0.020, OR = 2.11, dominant model after adjustment; p = 0.036, OR = 1.47, recessive model after adjustment; rs9468199: p = 0.008, OR = 1.52, allele model, p = 0.008, additive model, p = 0.007, OR = 0.22, recessive model, p = 0.005, OR = 0.20, recessive model after adjustment; rs34043159: p = 0.034, OR = 1.31, allele model, p = 0.036, additive model). Conclusion: Our study revealed that GALC, ZNF184, and IL1R2 were associated with PD in the southern Chinese population. GALC was also associated with LOPD. ELOVL7 and ZNF184 were associated with EOPD. In addition, trends of association to PD, between SATB1, NMD3, and FGF20, were also found. Statement of Significance: Genetic play an important role in the pathogenesis factors of Parkinson’s disease (PD). We found that GALC, ZNF184, and IL1R2 were associated with PD. GALC was also associated with late onset of PD, while ELOVL7 and ZNF184 were associated with early onset PD. This study is the first to find an association between GALC, ZNF184, and rs2280104 with PD.